Impact of contacts for message copies, mobile nodes and buffer size in delay-tolerant networks. (18th March 2021) - Hossen, Md. Sharif; Ahmad, Khaleel; Ahmad, Khairol Amali Bin
Delay tolerant network is a mobile ad hoc network where there are no predefined routes from one node to another, which is used in disaster and emergency communications. Here, we concentrate the analysis of node contact on contact duration aware routings techniques and address the issues of variation of mobile nodes, message copies and buffer size using ONE simulator. We observe that contact increases per hour with the increase of mobile nodes, while goes up and down for varying message copies and remains approximately the same for buffer size, i.e., buffer size does not affect the achievement of contacts. While, inter-contact time (ICT) is high at the beginning of communication for three cases, i.e. for varying message copies, mobile nodes and buffer size. Higher contact time results in higher ICT and number of contacts for varying mobile nodes, while it remains slightly changed for varying message copies and fixed for varying buffer size.